Dielectric constant, dielectric loss, conductivity, capacitance and model analysis of electronic electroactive polymers. (March 2023) - Wang, Hong; Yang, Liang
Abstract: In this study, the dielectric constant, dielectric loss, conductivity and capacitance of the electronic electroactive polymer (EEAP) were systematically tested experimentally, and the effects of different frequencies, effective voltages, electrode types, and specimen thicknesses on the dielectric relaxation properties of polymers were analyzed, and finally the Debye, Cole-Cole and Havriliak-Negami functions were used to model the dielectric constants. The experimental results show that the dielectric constant of the polymer depends strongly on the frequency, especially in the low frequency stage from 10 −1 to 100 Hz. The effect of different effective voltages on the dielectric properties is basically identical, and the accuracy of the test can be improved at this AC voltage avoiding the effect of electrostatic stress. At the same effective voltage and thickness, the polymer with G-C electrodes shows the best electrical parameters, the composite electrode form of G-C electrodes contributes to the conductive properties of the polymer and can be applied to the later design of actuators. Compared with the Debye model, the errors of the experimental and calculated values of the Cole-Cole and Havriliak-Negami models are smaller, 1.1102 and 0.7130, respectively. The dielectric behavior of EEAPs differs from that of epoxy materials, probably due to the influence of electric dipole moments, bound charges, and dipole effects. The paper has some reference value for further revealing the dielectric properties and relaxation time distribution of the polymer, and provides guidance for the later application of EEAP materials in flexible robots. Highlights: Systematically investigated the electrical properties of electroactive polymers. Deeply analyzed the relationship between relaxation and polarization. Analyzed and compared three modeling of dielectric constants.